2015
DOI: 10.1371/journal.pone.0123978
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Relative Dose-Intensity Reductions in Diffuse Large B-Cell Lymphoma Treated with R-CHOP21 or R-CHOP14

Abstract: DLBCL is an aggressive lymphoma treated with R-CHOP. Recently, attempts have been made to improve the outcome by increasing both dose-density and intensity but there have been no benefits in terms of survival. When treating malignancies RDI is important to consider but there is little published information on DLBCL. The purpose of this study was to analyze the differential prognostic impact of RDI in two cohorts of DLBCL patients treated with R-CHOP21 or R-CHOP14. From January 2001 to August 2013 we included D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
1
33
1
Order By: Relevance
“…To the best of our knowledge, this is the first report to evaluate between RDI and the clinical outcome in patients with advanced‐stage FL treated R‐CHOP. Several studies have found a correlation between the RDI of R‐CHOP and the clinical outcomes of diffuse large B‐cell lymphoma . However, in this study, we found no significant impact of RDI on patient outcomes in advanced‐stage FL.…”
Section: Baseline Patients' Characteristicscontrasting
confidence: 87%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report to evaluate between RDI and the clinical outcome in patients with advanced‐stage FL treated R‐CHOP. Several studies have found a correlation between the RDI of R‐CHOP and the clinical outcomes of diffuse large B‐cell lymphoma . However, in this study, we found no significant impact of RDI on patient outcomes in advanced‐stage FL.…”
Section: Baseline Patients' Characteristicscontrasting
confidence: 87%
“…Several studies have found a correlation between the RDI of R-CHOP and the clinical outcomes of diffuse large B-cell lymphoma. [10][11][12][13] However, in this study, we found no significant impact explanation is that patients with low tumor burden (who might be candidates for "watch and wait" strategy) were included.…”
mentioning
confidence: 86%
“…To characterize modifications of chemotherapy schemes, the concept of RDI, which reflects delivered DI divided by standard DI, has been introduced . A decrease in RDI in human patients with diffuse large B‐cell lymphoma who are treated with rituximab‐CHOP (R‐CHOP) is associated with poorer outcome . In 1 study in which dogs with lymphoma were treated with multidrug chemotherapy and half‐body irradiation, development of grade III or IV neutropenia was positively associated with remission duration, but RDI was not associated with outcome .…”
Section: Discussionmentioning
confidence: 99%
“…Lipocalin-2 from both myeloid cells and the epithelium combats Klebsiella pneumoniae lung infection in mice Elisabeth P. Cramer, 1 Sara L. Dahl, 1 Björn Rozell, 2 Kasper J. Knudsen, 3,4 Kim Thomsen, 5 Claus Moser, 5 Jack B. Cowland, 1,6 Lipocalin-2 is a eukaryotic siderophore-binding protein that prevents the growth and spread of microorganisms that require siderophoremediated uptake of soluble iron. 1 Consequently, lipocalin-2 knockout mice (Lcn2 2/2 mice) are more susceptible to infection with the siderophore-producing pathogen Klebsiella pneumoniae 2 than wildtype (WT) mice.…”
Section: To the Editormentioning
confidence: 99%
“…DLBCL is a curable disease in which relative dose intensity has been described to be associated with treatment efficacy. 2 However, clinicians may be concerned with the toxicity of high doses of anthracyclines in patients with elevated BSA.…”
mentioning
confidence: 99%